Analysis of Supplementary Feeding Satisfaction on Weight Gain and Reduction in the Incidence of Chronic Energy Deficiency in Pregnant Women - Feva Tridiyawati; Tria Shinta Angelina; Titin; Siti Rohani (Postgraduate, University of Mataram, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a global health issue affecting maternal and fetal health. Supplemental feeding (SF) is an intervention to address CED, but its success depends on maternal satisfaction with the program. This study analyzed the relationship between maternal satisfaction, weight gain, and reduction in CED incidence among pregnant women. Using a quantitative, cross-sectional design, 150 pregnant women from three health centers (Kutawaluyo, Kutamuki, Sukatani) were studied. Data were collected via questionnaires covering satisfaction with SF, weight gain, and nutritional status. Bivariate analysis showed a significant relationship between satisfaction with SF and weight gain (p = 0.04). Logistic regression revealed that satisfied mothers were 2.8 times more likely to achieve healthy weight gain than dissatisfied ones (OR = 2.8, p < 0.01). Maternal satisfaction was crucial for SF success in preventing CED. Psychosocial factors like communication between mothers and health workers and family support significantly influenced satisfaction levels. The study underscores the importance of tailoring SF programs to pregnant women’s needs and strengthening health policies to reduce CED prevalence. Enhanced maternal satisfaction with SF can improve nutritional outcomes, benefiting both mothers and their unborn children.